A six-step process for teaching vocabulary - D'Arcangelo, Marcia; Sheets, Dana; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2005)
This program demonstrates how teachers can use a six-step process recommended by Robert Marzano in his book, Building background knowledge for academic achievement: research on what works in schools, to teach academic vocabulary in the elementary or secondary grades. It also complements the Building academic vocabulary teacher's manual
Elementary (24 min.) -- Secondary (24 min.)
Title from title screen
Editor, Melanie Maholick ; associate producerm Ericha Bolinger
Keywords: Vocabulary -- Study and teaching (Elementary); Vocabulary -- Study and teaching (Secondary)